Vesicular release of glutamate mediates bidirectional signaling between astrocytes and neurons - Parpura, Vladimir (Henry Stewart Talks, 2012)
Neuronal glutamate release, Increases astrocytic intracellular Ca2+, Coordinates astrocytic network activity, Activates astrocytic plasma membrane glutamate transporters, Ca2+-dependent glutamate release from astrocytes, Increases neuronal intracellular Ca2+, Evokes a slow inward current in neurons, Increases neuronal excitability, Modulates spontaneous and evoked synaptic transmission, Promotes neuronal synchronization, Causes long-term potentiation of synaptic transmission
Reviewed at 2020/05/01